2012
DOI: 10.1159/000329555
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in the Dopamine System and Facial Expression Recognition in Healthy Chinese College Students

Abstract: Objective: This study investigated the relation between genetic variations in the dopamine system and facial expression recognition. Methods: A sample of Chinese college students (n = 478) was given a facial expression recognition task. Subjects were genotyped for 98 loci [96 single-nucleotide polymorphisms (SNPs) and 2 variable number tandem repeats] in 16 genes involved in the dopamine neurotransmitter system, including its 4 subsystems: synthesis (TH, DDC, and DBH), degradation/transport (COMT,MAOA,MAOB, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
1
9
0
1
Order By: Relevance
“…boys), but with disgust having the highest significance (p . 0.0000) (22). Looking at our two groups it can be seen that all three girls in the present study are found in Group 1, accounting here for even 1 of the 3 of the group's participants.…”
Section: Disgustsupporting
confidence: 54%
See 1 more Smart Citation
“…boys), but with disgust having the highest significance (p . 0.0000) (22). Looking at our two groups it can be seen that all three girls in the present study are found in Group 1, accounting here for even 1 of the 3 of the group's participants.…”
Section: Disgustsupporting
confidence: 54%
“…Moreover, the basic concept of the Theory of Mind is seen partly to lie in the dopaminergic pathway (28), with changes in this neurotransmitter system having a direct effect on the emotion recognition abilities (22). Lackner et al (28) demonstrated a direct correlation between the length of the DRD4-allele (of the dopamine receptor) and the Theory of Mind abilities.…”
Section: Neutralmentioning
confidence: 99%
“…2009; Zhu et al. 2012). Both phenomena have been related to various disorders where affective processing plays a relevant role (e.g., Demenescu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Affective priming has been extensively used to examine the automatic affective processing (Fazio 2001;Klauer and Musch 2003) and refers to the fact that the time needed to evaluate a target item is shorter when it is preceded by an affectively congruent prime than when it is preceded by an affectively incongruent prime. Recognition of facial expressions plays a key role in the communication of emotions, and is subjected to both environmental and genetic influences (Ekman 1993;Lau et al 2009;Zhu et al 2012). Both phenomena have been related to various disorders where affective processing plays a relevant role (e.g., Demenescu et al 2010;Hooker et al 2011;LeMoult et al 2012), suggesting that they could be endophenotypes underlying deviant phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1918, Fisher proposed this polygenic model that combined many genes of small effects to yield the continuous variation for most quantitative traits [45]. Recently, some studies have successfully applied the polygenic model by combining effects of the whole genome [46], [47], [48] or effects of genes within a pathway [49], [50], [51]. Since several serotonin-related genes exert their effect on BMI, it is likely that their effects are cumulative.…”
Section: Introductionmentioning
confidence: 99%